Religiöse Erfahrung und ihre transformative Kraft Qualitative und hermeneutische Zugänge zu einem praktisch-theologischen Grundbegriff - Müller, Sabrina (Praktische Theologie im Wissenschaftsdiskurs, 2023)
The author approaches the phenomenon of 'religious experience' through a qualitative study in which young, urban people from Europe and the USA are empirically examined. It becomes clear that individuals themselves are constructive agents of experience and theology. Religious experience manifests itself as a transformative perspective of hope in the lives of young people.